The Implications of Village Regulation toward the Dualism of Local Leadership Dynamics - I Nyoman Subanda; I Nyoman Budiana; A.A.Ngr Eddy Supriyadinata Gorda (Udayana Journal of Law and Culture, 2020)
The transformation of local leadership in Bali has implications for the emergence of various phenomena of the relationship of desa dinas (the official administrative village) and desa adat (the customary village) which both have autonomous rights. The authority of desa adat and desa dinas coincides with each other. With these conditions, various potential conflicts, poor communication patterns, and overlapping authority are very likely to occur at the local level. In this study, several issues will be discussed, namely: What is the model and process of transformation in local leadership especially in desa adat in Bali? What is the process and form of negaranisasi in local leadership especially in desa adat in Bali? What are the competencies and roles of local leaders in the local leadership process in Bali? What are the roots, the causes and solutions in handling horizontal conflicts in local leadership in Bali? Data were collected by interview, documentation and focus group discussion method to obtain sufficient data variance and validity. Furthermore, the data were analyzed qualitatively using interactive models from Miles and Huberman. The results of the study can be described, that the synergy of two (2) types of local leadership is needed. The capacity and competence of village officials and prajuru adat (customary officials) are obliged to be enhanced, strengthened and empowered, so that they are able to adapt in handling various problems that arise in rural communities in the era of modernization and globalization. For this reason, it is needed to build a synergic relationship model and leadership coordination system between desa dinas and desa adat, a model for developing the capacity and competency of village officials and prajuru adat, and developing a model for handling conflicts that have increasingly intense.